Crack: práticas educativas e culturais na trajetória de um dependente - Ferreira, Tereza Maria da Silva (2014)
This research aims investigating the educational and cultural practices from crack users, by the biography of a addict, focusing the contexts and paths that evolved this use, relating sociocultural facts and determinants which collaborate in the memory and life history of the biography subject. It has as theoretical contribution approaches from several authors and several fields of knowledge, as Healthy, Sociology and Education. By the fact the biography subject is a homeless, the study was accomplished in many places, from bars, steakhouses, the family residence, and even near the called “bocas de fumo”. By treating this as a qualitative research, the methodological approach is the life history and the data collection is proceeded on the basis of the biographical oral history, accomplished by the open interview and field journal. In this way, the data analysis is guided in concepts and central categories related to the biography crack addict’s speech. In the path’s analysis of drug using in the speech of Bin Guerra, it was important for us to know some aspects that helped to understand the reason why people still use drugs, despite all its negativity and the committed efforts to fight against this using. It must be considered the “different subjects” and the subjectivity involved when they make use of these substances, as the diverse cultural, educative contexts, vulnerability phase that surrounds teenagers and permeates that reality based on the study topics. Concluding the analysis, it was noticed that even we cannot affirm that the crack use can become a practice resulted of other kinds of drugs, we cannot deny the experience opportunity with other kind of drug allows to favor this practice. It is essential to consider, in the speech of Bim Guerra, the importance of family role in the relation of behavior/educational development, concerning the involvement with the use of drugs.